Interhemispheric Asymmetry of Brain Diffusivity in Normal Individuals: A Diffusion-Weighted MR Imaging Study - Fabiano, Andrew J.; Horsfield, Mark A.; Bakshi, Rohit (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Previous neuroimaging studies have suggested asymmetries in brain diffusivity may exist. The purpose of this study was to assess whether water diffusivity in deep gray matter structures shown by diffusion-weighted (DW) imaging differs between the right and left cerebral hemispheres in normal individuals.METHODS: Brain MR imaging was obtained in 23 healthy volunteers. A multisection image without diffusion weighting, and images with weighting applied in the read, phase, and section directions with a b-factor of 1000 s/mm2 were collected. Diffusivity was computed separately in each direction, and the results were averaged to form mean diffusivity maps. Quantitative diffusivity values were obtained from the globus pallidus, putamen, caudate, thalamus, white matter, and CSF by using a standardized region of interest template. Interhemispheric differences were assessed by using a paired sample t test.RESULTS: Mean diffusivity was higher in the: left (mean ± SD: 0.689 × 10−3± 0.069 × 10−3mm2/s) versus right (0.642 × 10−3± 0.071 × 10−3mm2/s) caudate (% difference, P value: 7.0%, P = .001); right (0.745 × 10−3± 0.053 × 10−3mm2/s) versus left (0.706 × 10−3± 0.050 × 10−3mm2/s) globus pallidus (5.2%, P < .001); left (0.720 × 10−3± 0.059 × 10−3mm2/s) versus right (0.674 × 10−3± 0.052 × 10−3mm2/s) putamen (6.4%, P < .001); right (0.750 × 10−3± 0.040 × 10−3mm2/s) versus left (0.716 × 10−3± 0.031 × 10−3mm2/s) thalamus (4.5%, P < .001). No significant right versus left difference was seen in the CSF (P = .291), anterior frontal white matter (P = .834), or centrum semiovale (P = .320).CONCLUSION: Gray matter diffusivity may differ between hemispheres of the brain in healthy individuals. Analysis of deep gray matter lesions requires caution, as statistically significant interhemispheric differences may not always be indicative of disease.